Variação linguística na EJA: estigma ou aceitabilidade - Stacheski, Viviane Schueda (2014)
The aim of this research has been reflecting about young and adult Portuguese Language research, focused on sociolinguistics features, especially on linguistic variation, after analysing several comments made about the textbook "Por uma vida melhor", which, caused a lot of controversy in May 2011. For that, it has also been pursued bassing on studies made by Labov, Preti, Bagno, Mussalim, among other important writers of this area. The sociolinguistics features on public politcs which regulate the National Education have been investigated in order for there to be sufficient degree of those given on Mother Language Teaching, especially oral skills. After theorical considerations, good progress has also been made in analysing questionnaires answered by EJA students and workers responsible for hiring people on business areas in order to verify how EJA graduating people and nonvalued oral standard language users are accepted by commercial branch. It has also been pursued observing oral skills have been developed in schools. The questionnaire results have shown that nonstandard language is a more excluding factor than EJA Education.